Identification of a novel polyomavirus from a marsupial host - Dunowska M; Perrott M; Biggs P (Oxford University Press, 2022)
We report the identification and analysis of a full sequence of a novel polyomavirus from a brushtail possum (Trichosurus vulpecula) termed possum polyomavirus (PPyV). The sequence was obtained from the next-generation sequencing assembly during an investigation into the aetiological agent for a neurological disease of possums termed wobbly possum disease (WPD), but the virus was not aetiologically involved in WPD. The PPyV genome was 5,224 nt long with the organisation typical for polyomaviruses, including early (large and small T antigens) and late (Viral Protein 1 (VP1), VP2, and VP3) coding regions separated by the non-coding control region of 465 nt. PPyV clustered with betapolyomaviruses in the WUKI clade but showed less than 60 per cent identity to any of the members of this clade. We propose that PPyV is classified within a new species in the genus Betapolyomavirus. These data add to our limited knowledge of marsupial viruses and their evolution.
Keywords: Betapolyomavirus; WUKI clade; marsupial virus; polyomavirus; possum; virus taxonomy